The quality of research in sports journals - Bleakley, C.; MacAuley, D. (British Journal of Sports Medicine, 2002)
Objective: To examine the evidence base of sports medicine research. Methods: A sample of four major journals that present core research in sport and exercise medicine (British Journal of Sports Medicine, Medicine and Science in Sports and Exercise, Journal of Sports Medicine and Physical Fitness, and Physical Therapy) was examined using assessment criteria taken from the READER method. Results: Randomised controlled trials comprised 10% or less of all original research articles. Observational/descriptive studies were the most commonly published study design. There was a highly significant difference (p<0.0001) in the contents of the four journals but when they were compared by categorising the better quality methods together (randomised control trial, case-control, and cohort studies), the difference was not significant (p = 0.09). Conclusions: The overall pattern of publication type seems remarkably stable over medical journals, indicating that the quality of sports medicine research is comparable to that in other specialities.